2012
DOI: 10.3389/fneur.2012.00111
|View full text |Cite
|
Sign up to set email alerts
|

Acute Minocycline Treatment Mitigates the Symptoms of Mild Blast-Induced Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) represents a significant challenge for the civilian and military health care systems due to its high prevalence and overall complexity. Our earlier works showed evidence of neuroinflammation, a late onset of neurobehavioral changes, and lasting memory impairment in a rat model of mild blast-induced TBI (mbTBI). The aim of our present study was to determine whether acute treatment with the non-steroidal anti-inflammatory drug minocycline (Minocin®) can mitigate the neurobehavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 184 publications
(241 reference statements)
6
107
1
1
Order By: Relevance
“…To our knowledge, this is the first study to examine delayed immunosuppression at long-term injury time points, because other immunosuppressive treatments targeting anxiety-like behaviors have been administered before or within hours of injury. 34,37,38,[66][67][68][69] These results indicate that the persistence of post-traumatic anxiety may reflect chronic neuroinflammatory neuropathy, a possibility supported by the observation of activated microglia and astrocytes, key cells mediating inflammatory processes, many years after injury in long-term survivors of TBI. [9][10][11][12] Chronic post-traumatic neuroinflammation suggests the presence of a self-perpetuating positive feedback loop, possibly involving reactivation and further promotion of inflammatory mediators after injury in an inflammation-damage-inflammation cycle.…”
Section: Discussionmentioning
confidence: 73%
“…To our knowledge, this is the first study to examine delayed immunosuppression at long-term injury time points, because other immunosuppressive treatments targeting anxiety-like behaviors have been administered before or within hours of injury. 34,37,38,[66][67][68][69] These results indicate that the persistence of post-traumatic anxiety may reflect chronic neuroinflammatory neuropathy, a possibility supported by the observation of activated microglia and astrocytes, key cells mediating inflammatory processes, many years after injury in long-term survivors of TBI. [9][10][11][12] Chronic post-traumatic neuroinflammation suggests the presence of a self-perpetuating positive feedback loop, possibly involving reactivation and further promotion of inflammatory mediators after injury in an inflammation-damage-inflammation cycle.…”
Section: Discussionmentioning
confidence: 73%
“…To our knowledge, this is the first study to examine delayed immunosuppression at long-term injury time points, because other immunosuppressive treatments targeting anxiety-like behaviors have been administered before or within hours of injury. 34,37,38,[66][67][68][69] These results indicate that the persistence of post-traumatic anxiety may reflect chronic neuroinflammatory neuropathy, a possibility supported by the observation of activated microglia and astrocytes, key cells mediating inflammatory processes, many years after injury in long-term survivors of TBI. [9][10][11][12] Chronic post-traumatic neuroinflammation suggests the presence of a self-perpetuating positive feedback loop, possibly involving reactivation and further promotion of inflammatory mediators after injury in an inflammation-damage-inflammation …”
Section: Discussionmentioning
confidence: 89%
“…However, there have been recent seminal reports by Vink and colleagues (63-65) of post-traumatic anxiety-like behavior in rats using an impact-acceleration model of diffuse TBI and noting significant decreases in open field exploration due to freezing (a natural defensive fear response of rats). Several other groups have since reported similar post-traumatic anxiety in rodents using a variety of TBI methods, postinjury measurement time-points, and behavioral measures (66)(67)(68)(69)(70). Freezing behavior was not measured directly in these studies, although freezing was consistently reported to cause decreased exploratory behavior in the open field test (63)(64)(65), suggesting a dominant fear response that is associated with pathological anxiety.…”
Section: Post-traumatic Anxiety Is a Leading And Devastating Consequementioning
confidence: 99%
See 1 more Smart Citation
“…In a study examining the use of minocycline in a blast injury model of TBI in rats, researchers noted a decrease in post-TBI anxiety via the elevated plus maze at 46 days post-injury accompanied by decreased corticosterone levels and improvements in spatial memory via Barnes maze testing post-injury as late as 47 days post-TBI [237]. Minocycline administration also decreased inlammatory and neuron and glial injury-associated markers c-reactive protein, monocyte-chemotactic protein-1, neuron-speciic enolase, S100 β, tau, and neuroilament H in this study [237].…”
Section: The Antibiotic Minocycline In Ais and Tbimentioning
confidence: 99%